TUGAS DAN WEWENANG DINAS KELAUTAN DAN PERIKANAN PROVINSI SUMATERA UTARA DALAM PELAKSANAAN OTONOMI DAERAH DI BIDANG USAHA PERIKANAN - Achmad Reza Pradana, Amiek Soemarmi, Indarja (Diponegoro Law Journal, 2012)
North Sumatera province is one of the autonomous area that potential within fishery sector and that have the authority to manage their own potential sea as defined in Article 18 Act Number 32, 2004 states that the area that have sea area was given authority to manage resource in sea area. Fishery and naval department of North Sumatera Province carried out local administration affairs/province authority within cultivation fishery sector, fishery catch, monitoring, both fishery and naval resource controlling and management in coastal area also small islands and assistance task. Fishery and Naval Department Implementation in arrange fishery business in North Sumatera area are by issued fishery business license including catch and cultivation fisheries, carried out monitoring to catching fishery business, making and implement related to fishery business policy, carried out development and training to fishermans.